2018
DOI: 10.1007/s00264-018-3993-9
|View full text |Cite
|
Sign up to set email alerts
|

The modified Dunn procedure provides superior short-term outcomes in the treatment of the unstable slipped capital femoral epiphysis as compared to the inadvertent closed reduction and percutaneous pinning: a comparative clinical study

Abstract: Compared to inadvertent reduction and percutaneous pinning, the modified Dunn procedure provided better clinical and radiographic outcomes with similar proportion of osteonecrosis and unplanned re-operations following an unstable SCFE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 26 publications
0
28
0
Order By: Relevance
“…An increasing number of articles have appeared in the literature on the treatment of SCFE with surgical dislocation2,5,43,55,6166 demonstrating that this technique is effective. Novais et al67 compared children with severe stable SCFE treated with the modified Dunn procedure or in situ pinning in terms of proximal femoral radiographic deformity, Heyman and Herndon clinical outcome, complication rate, and number of reoperations performed after the initial procedure.…”
Section: Treatmentmentioning
confidence: 99%
“…An increasing number of articles have appeared in the literature on the treatment of SCFE with surgical dislocation2,5,43,55,6166 demonstrating that this technique is effective. Novais et al67 compared children with severe stable SCFE treated with the modified Dunn procedure or in situ pinning in terms of proximal femoral radiographic deformity, Heyman and Herndon clinical outcome, complication rate, and number of reoperations performed after the initial procedure.…”
Section: Treatmentmentioning
confidence: 99%
“…Subcapital osteotomies (modified Dunn) have been shown to provide good clinical and radiographic outcomes for treating severe and unstable slips when compared to in situ fixation. ( 8 …”
Section: Discussionmentioning
confidence: 99%
“…However, it is important to note that in the acute moderate to severe unstable SCFE, there is a baseline 20 to 50% risk of AVN with closed reduction followed by pinning [34,52]. A recent study comparing in situ pinning to modified Dunn in these patients showed a comparable AVN rate, but less femoral-sided deformity and better shortterm hip function in the patients undergoing modified Dunn [53]. Parsh also recently described an anterior open-reduction technique for the moderate to severe unstable SCFE that had excellent short-term clinical outcomes with low proportion of avascular necrosis and appropriate restoration of femoral anatomy [54].…”
Section: Treatmentsmentioning
confidence: 99%
“…While early studies on the outcome of the modified Dunn mostly came from Switzerland with excellent results [38••, 57], there have been multiple reports over the last few years on outcomes from other centers [53,58,59], They have mostly reported favorable outcomes and restoration of more appropriate femoral anatomy [58]. Because of these results from multiple centers, acute realignment of the moderate to severe acute SCFE with contemporary open-reduction techniques is becoming a viable treatment option to restore femoral anatomy where proper expertise is available.…”
Section: Treatmentsmentioning
confidence: 99%
See 1 more Smart Citation